Facile synthesis of tea waste/Fe3O4 nanoparticle composite for hexavalent chromium removal from aqueous solution. Issue 13 (23rd January 2017) - Fan, Shisuo; Wang, Yi; Li, Yang; Tang, Jun; Wang, Zhen; Tang, Jie; Li, Xuede; Hu, Kai
Abstract : A tea waste/Fe3 O4 composite was prepared through chemical co-precipitation approach and was used for Cr(vi ) removal, involving an adsorption-coupled reduction mechanism. Abstract : The modification of biomass waste, as a multifunctional composite, has received tremendous attention for resource utilization and recycling. In this study, tea waste, which is a high level generator of biomass waste, was loaded with nano-Fe3 O4 particles to prepare a magnetic tea waste/Fe3 O4 (TW/Fe3 O4 ) composite through a facile chemical co-precipitation approach. BET, SEM, TEM, XRD, magnetic properties, FTIR, XPS were used to characterize the TW/Fe3 O4 composite. A superparamagnetic TW/Fe3 O4 composite (Fe3 O4 : about 20 nm) was successfully synthesized and possessed the advantages of tea waste and nano-Fe3 O4 particles. A chromium(vi ) adsorption experiment showed that this material has a strong adsorption capacity for aqueous chromium ions, which reached 75.76 mg g −1 based on the Langmuir model. The adsorption process could be well fitted by a pseudo-second-order kinetic model and Langmuir, Temkin and Dubinin–Radushkevich (D–R) isotherm models, and was spontaneous and endothermic according to the thermodynamic analysis. The TW/Fe3 O4 composite revealed good reusability and the removal rate was more than 70% after five recycling cycles. The mechanism of Cr(vi ) removal involved electrostatic attraction, reduction process, ion exchange, surface complexation, etc. 70% of Cr(vi ) was reduced to Cr(iii ) in this investigation. This study indicated that a TW/Fe3 O4 composite could be an attractive option for heavy metal treatment.